Whole transcriptome sequencing reveals HOXD11-AGAP3, a novel fusion transcript in the Indian acute leukemia cohort - Desai, Sagar Sanjiv; Ravindran, Febina; Panchal, Amey; Ojha, Nishit; Jadhav, Sachin; Choudhary, Bibha (Frontiers in Genetics, 2023)
Introduction: Acute leukemia is a heterogeneous disease with distinct genotypes and complex karyotypes leading to abnormal proliferation of hematopoietic cells. According to GLOBOCAN reports, Asia accounts for 48.6% of leukemia cases, and India reports ~10.2% of all leukemia cases worldwide. Previous studies have shown that the genetic landscape of AML in India is significantly different from that in the western population by WES. Methods: We have sequenced and analyzed 9 acute myeloid leukemia (AML) transcriptome samples in the present study. We performed fusion detection in all the samples and categorized the patients based on cytogenetic abnormalities, followed by a differential expression analysis and WGCNA analysis. Finally, Immune profiles were obtained using CIBERSORTx. Results: We found a novel fusion HOXD11-AGAP3 in 3 patients, BCR-ABL1 in 4, and KMT2A-MLLT3 in one patient. Categorizing the patients based on their cytogenetic abnormalities and performing a differential expression analysis, followed by WGCNA analysis, we observed that in the HOXD11-AGAP3 group, correlated co-expression modules were enriched with genes from pathways like Neutrophil degranulation, Innate Immune system, ECM degradation, and GTP hydrolysis. Additionally, we obtained HOXD11-AGAP3-specific overexpression of chemokines CCL28 and DOCK2. Immune profiling using CIBRSORTx revealed differences in the immune profiles across all the samples. We also observed HOXD11-AGAP3-specific elevated expression of lincRNA HOTAIRM1 and its interacting partner HOXA2. Discussion: The findings highlight population-specific HOXD11-AGAP3, a novel cytogenetic abnormality in AML. The fusion led to alterations in immune system represented by CCL28 and DOCK2 over-expression. Interestingly, in AML, CCL28 is known prognostic marker. Additionally, non-coding signatures (HOTAIRM1) were observed specific to the HOXD11-AGAP3 fusion transcript which are known to be implicated in AML.